Representations of prisoner hero in the novel (Eastern Mediterranean) (By the novelist Abdul-Rahman Munif) - Nizar Frak Ali; Oday Kamil Hammadi; Riyadh Hamzah Abbood (Genius Journals, 2021)
This study tries to interrogate one of the important Arab novels, which is the novel (Eastern Mediterranean) by the great novelist (Abdul- Rahman Munif) and the narrative work in a way that shows the great value that novel contains in representations of the political side and its reflection on character of the hero and movement of narration within a novel as well as the relationship of the heroine character to both jail and jailer alike, who represents on the other about heroine character, and how to express the repressed freedoms within structure of the novel, as well as explaining the concept of heroism and its content, in a different way from what was usual for reader or recipient.
Keywords: reflection; heroine; great novelist; Arab